Direct linkage of mitochondrial genome variation to risk factors for type 2 diabetes in conplastic strains - Pravenec, Michal; Hyakukoku, Masaya; Houštěk, Josef; Zídek, Václav; Landa, Vladimír; Mlejnek, Petr; Mikšík, Ivan; Mothejzíková, Kristýna; Pecina, Petr; Vrbacký, Marek; Drahota, Zdeněk; Vojtíšková, Alena; et al. (Genome research, 2007)
Recently, the relationship of mitochondrial DNA (mtDNA) variants to metabolic risk factors for diabetes and other common diseases has begun to attract increasing attention. However, progress in this area has been limited because (1) the phenotypic effects of variation in the mitochondrial genome are difficult to isolate owing to confounding variation in the nuclear genome, imprinting phenomena, and environmental factors; and (2) few animal models have been available for directly investigating the effects of mtDNA variants on complex metabolic phenotypes in vivo. Substitution of different mitochondrial genomes on the same nuclear genetic background in conplastic strains provides a way to unambiguously isolate effects of the mitochondrial genome on complex traits. Here we show that conplastic strains of rats with identical nuclear genomes but divergent mitochondrial genomes that encode amino acid differences in proteins of oxidative phosphorylation exhibit differences in major metabolic risk factors for type 2 diabetes. These results (1) provide the first direct evidence linking naturally occurring variation in the mitochondrial genome, independent of variation in the nuclear genome and other confounding factors, to inherited variation in known risk factors for type 2 diabetes; and (2) establish that spontaneous variation in the mitochondrial genome per se can promote systemic metabolic disturbances relevant to the pathogenesis of common diseases.
Keywords: Animals; Gene Dosage; substituce aminokyselin; Rats, Inbred BN; haplotypy; sekvenční analýza DNA; genová dávka; genom; genetická variace; financování organizované; Electron Transport Complex IV; Polymorphism, Genetic; zvířata; diabetes mellitus 2. typu; Sequence Analysis, DNA; Diabetes Mellitus, Type 2; Genetic Variation; mitochondriální DNA; Base Sequence; Financing, Organized; respirační komplex IV; DNA, Mitochondrial; Rats; rizikové faktory; Male; sekvence nukleotidů; Mitochondria; mitochondrie; Risk Factors; polymorfismus genetický; potkani inbrední BN; Amino Acid Substitution; krysa rodu Rattus; Haplotypes; potkani inbrední SHR; Rats, Inbred SHR; mužské pohlaví; Genome